Dietary Intake across Reproductive Life Stages of Women in India: A Cross-Sectional Survey from 4 Districts of India. (29th June 2020) - Sharma, Shantanu; Akhtar, Faiyaz; Singh, Rajesh Kumar; Mehra, Sunil
Abstract : Nutritional deficiencies among women of reproductive age, especially from socially backward classes, are widely prevalent in India. The present study aimed to assess the nutrient intakes and analyse their associations with sociodemographic attributes among socially backward adolescent girls, newly married women, pregnant women, and lactating mothers from four districts of India. Further, the study looked at the associations between nutrient intakes and anthropometric measurements (body mass index, BMI; waist circumference; and waist-hip ratio, WHR) among adolescents and newly married women. This community-based cross-sectional study used the 24-hour recall method of the dietary survey to assess the food intake of women and girls. Nonparametric tests of associations between sociodemographic characteristics and the median nutrient intakes were conducted. Expected and observed increments in energy and nutrient intakes of pregnant and lactating women from the base (requirement of an adult woman) were calculated. A total of 477 pregnant women, 455 lactating mothers, 532 newly married women, and 223 adolescent girls were interviewed. According to the 24-h dietary recall, only 35% of adolescent girls, 57% newly married women, 40% pregnant women, and 34% lactating mothers were able to meet 70% of the recommended energy requirements. A large percentage of pregnant women had less than 50% of the recommended intakes of iron, calcium, and folic acid. Women living in nuclear families, urban slums, and those from backward classes had lower intakes of almost all the nutrients compared to their counterparts (p < 0.001 ). There were no significant differences in the nutrient intakes of adolescents, newly married, pregnant, and lactating women, and all had poor dietary intakes. We found positive relationships of all three anthropometric measurements (BMI, waist circumference, and WHR) with fats and inverse associations with carbohydrates. Public health interventions should work towards improving the nutrition of these vulnerable populations.